ANALISIS KINERJA DAN TINGKAT KESIAPAN RANTAI PASOK (SUPPLY CHAIN) KOMODITAS KAKAO (THEOBROMA CACAO L.) DI ERA REVOLUSI INDUSTRI 4.0 - Muhammad Muhajirin Saing; Ansyar Ansyar (Ensiklopedia of Journal, 2022)
The purpose of this study is to identify the characteristics and performance of the cocoa supply chain in Polewali Mandar Regency, West Sulawesi, and the level of readiness of the cocoa supply chain in Polewali Mandar Regency, West Sulawesi in the Industrial Revolution Era 4.0.. The analytical method used is the characteristics and performance of the supply chain with qualitative descriptive analysis using the FSCN (Food Supply Chain Networking) analytical framework and the level of readiness of key stakeholders in facing the industrial revolution 4.0 with a simple quantitative analysis with a scoring and percentage system with Microsoft Excel. The results showed that the supply chain of cocoa beans in Polewali Mandar Regency currently consists of farmers, collectors, wholesalers and exporters/processing industries. Supply chain performance on channel I shows more effective and efficient performance. The marketing margin in this channel is the smallest compared to other channels, which is Rp. 28,045/kg, while Farmer's share is 100% which is the highest compared to other channels. Channel I is a channel from farmers who directly sell to the final consumer, namely the purchasing unit (exporter & processing industry). The highest level of readiness in facing the industrial revolution 4.0 is the exporter/processing industry (96.3%). while others are classified as low, namely wholesalers (11.11%), collector traders (6.79%) and farmers (4.44%).Keywords: Cocoa, Supply Chain, Industrial Revolution 4.0, Stakeholders